Penyuluhan Hukum Etika Pergaulan Remaja Perspektif Islam: Legal Counseling on Adolescent Social Ethics from an Islamic Perspective - Sanawiah, Sanawiah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The challenges that are most felt by teenagers are not only about mental maturity and quality supplies that are ready to use but also other things such as financial readiness, maturity in thinking, wisdom in making decisions and many more. Of course, preparation and preparedness is needed in learning everything that may be needed for life in the future. Neglecting social ethics by teenagers does not rule out the possibility that most of them will not be able to face the negative influences of friends and the environment, so there will be big problems that violate morals not only for themselves but also their parents, family and the surrounding community. Providing legal counseling held by the Legal Aid Post (POSBAKUM). Aisyiyah Central Kalimantan and Lecturer at Muhamamdiyah University Palangkaraya is a form of concern for young people, especially teenagers, which aims to provide students with an understanding of the dangers of promiscuity and provide students with an understanding of ethics in social relations and the impact of promiscuity according to Islamic law. The methods used in this community service are lecture, discussion and question and answer methods.